RME dan capcut: Optimalisasi kemampuan pemecahan masalah matematis - Sopika, Riris; Hendriana, Heris; Chotimah, Siti (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2024)
The purpose of this study is to combine the RME approach with the use of the CapCut application in an effort to optimize students' mathematical problem-solving skills. Realistic Mathematics Education is an approach that uses the real world to understand and solve problems. The population in this study of students at SMPN 1 Cihampelas the sample used is class VIII students with a total of 40 students. The learning instruments and tools used are Pretest and Postes questions and LKPD which contain material about the Pythagorean theorem and the characteristics of the Realistic Mathematics Education approach. The results of the Mann-Whitney test analysis prove that the improvement of mathematical problem-solving skills of grade VIII students whose learning uses the Realistic Mathematics Education approach assisted by CapCut learning videos is better than students who use regular learning. So that the RME and CapCut approaches are able to optimize students' mathematical problem-solving skills.